2005
DOI: 10.1124/jpet.105.091363
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Donating Aspirin Inhibits Colon Cancer Cell Growth via Mitogen-Activated Protein Kinase Activation

Abstract: Nitric oxide-donating aspirin (NO-aspirin), representing a new concept in the development of more efficacious nonsteroidal anti-inflammatory drugs, consists of traditional aspirin bearing -ONO 2 , which releases NO. Conventional aspirin prevents human colon cancer, but its toxicity precludes its application as a chemopreventive agent. NO-aspirin seems safer and in cultured cancer cells it is Ͼ1000-fold more potent than aspirin. To determine the mechanism by which NO-aspirin inhibits cell growth, we studied its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…Numerous evidences revealed strong antineoplastic properties of NSAIDs modified by covalent attachment of NO (6,8,9,12,30). In this study, we showed for the first time that chemical modification of parental isoxazole acetic acid derivative VGX-1027 created a qualitatively new NOdonating compound possessed strong antitumor potential.…”
Section: Discussionmentioning
confidence: 76%
“…Numerous evidences revealed strong antineoplastic properties of NSAIDs modified by covalent attachment of NO (6,8,9,12,30). In this study, we showed for the first time that chemical modification of parental isoxazole acetic acid derivative VGX-1027 created a qualitatively new NOdonating compound possessed strong antitumor potential.…”
Section: Discussionmentioning
confidence: 76%
“…Guggulsterone has been shown to suppress growth of cancer cells including acute myeloid leukemia and PC-3 human prostate cancer cell lines by causing apoptosis (32,34) but the sequence of events leading to cell death is poorly defined. To gain insights into the mechanism of guggulsterone-induced apoptosis, we determined its effect on activating phosphorylations of JNK1/2 (Thr 183 /Tyr 185 ), p38 MAPK (Tyr 182 ), and ERK1/2 (Tyr 204 ), which are implicated in regulation of cell survival and apoptosis by different stimuli including various cancer preventive agents (35)(36)(37)(38)(39)(40). Figure 1A (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, recent in vitro work has indicated that NOaspirin has a major effect on the mitogen-activated protein kinase pathway affecting the activation of c-Jun and activating transcription factor-2, two proteins that participate in the formation of the activator protein complex (46).…”
Section: Discussionmentioning
confidence: 99%